Ciclagem do nitrogênio relacionada ao sistema de produção - Pivetta, Laércio Augusto [UNESP] (2015)
The knowledge of how soil management acts upon N cycling in long term can provide bases to develop crop production systems that optimize the cycling of this nutrient. The objective of this research was to assess the effect of soil management systems, using cover crops and chiseling in rotation with soybean on N cycling and balance. The experiment has been carried out since 2003, on a clayey Rhodic Nitosol. The experimental design was a randomized complete block design, in a split‑plot arrangement, with four replicates. Plots consisted of the fall-winter crops, triticale (X Triticosecale) and sunflower (Helianthus annuus), and subplots of the spring managements, pearl millet (Pennisetum glaucum), forage sorghum (Sorghum bicolor) and sunn hemp (Crotalaria juncea), besides chiseling in 2003 and 2009, at the spring too. Soybean (Glycine max) was grown in the summer. The N cycling and balance were studied by determinations of soil total-N and N storage, dry mass and N accumulation of crops and its residues, grain yield and N exportation by fall-winter crops and soybean, N outputs by NO3- leaching and NH3 and N2O emission, besides N inputs by atmospheric deposition, pesticide spraying and seeds. Losses of N ranged from 1.2 to 3.3, 8.2 to 8.9 and 12.2 to 50.4 kg ha-1 year-1 as N2O, ...